2022
DOI: 10.1002/celc.202200121
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Electrochemical Detection of Carcinoembryonic Antigen with a Label‐Free Immunosensor Using Gold Nanoparticle‐Decorated Poly(pyrrole‐co‐3,4‐ethylenedioxythiophene)

Abstract: In this study, an electrochemical immunosensor was developed using gold nanoparticles (AuNPs), 3,4-ethylenedioxythiophene (EDOT), and pyrrole (Py) to detect carcinoembryonic antigen (CEA) sensitively. Firstly, the electrocopolymerization of PPy and EDOT was carried out on a pencil graphite electrode (PGE) by the chronoamperometry method (p(Py-co-EDOT)/PGE). Then, gold nanoparticles were electrochemically deposited on the prepared p(Py-co-EDOT)/PGEs by the chronoamperometry method. The characterizations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…S2c), it was found that the pair peak at 84.4 and 91 eV correspond to Au 4f7/2 and Au 4f5/2 , respectively, indicating the presence of elemental gold (Au 0 ). 48,49 Fourier transform infrared spectroscopy (FTIR) was used to identify functional groups on the surface of the developed CuO/S-G/AuNPs/ SPE. Upon examination of the spectrum presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2c), it was found that the pair peak at 84.4 and 91 eV correspond to Au 4f7/2 and Au 4f5/2 , respectively, indicating the presence of elemental gold (Au 0 ). 48,49 Fourier transform infrared spectroscopy (FTIR) was used to identify functional groups on the surface of the developed CuO/S-G/AuNPs/ SPE. Upon examination of the spectrum presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the strong adsorption bands at 1989, 2069, and 2118 cm À1 in the spectrum belong to (-C-H-) stretching. 28 The FTIR spectra of p(EDOT-co-3MT)/PGE and AuNPs/p(EDOT-co-3MT)/PGE exhibit characteristic bands at 1463 cm À1 and 1369 cm À1 , respectively, which can be attributed to the CQC and C-C stretching vibrations of the thiophene ring. 29 Additionally, the spectra show characteristic peaks at 994 cm À1 and 864 cm À1 , which correspond to the C-S stretching mode.…”
Section: Characterization Of the Aunps/p(edot-co-3mt)/pgementioning
confidence: 98%
“…The XPS technique is widely used to determine electrode features, specifically valence, by revealing the binding energies of component atoms and ions. 28 Fig. 2a-c display the XPS survey, S2p sub-binding, and Au4f core-level spectra, respectively.…”
Section: Characterization Of the Aunps/p(edot-co-3mt)/pgementioning
confidence: 99%
“…In addition, when the images are analyzed carefully, it is possible to see the edges of the layers of GO. 34 In addition, as the amount of graphene oxide increases and accumulates, the brightness also increases. The hydroxyl part of the carboxylic acid in the graphene oxide structure and the oxygen of the hydroxyl groups on the surface of the polyester/cotton blended fabric form a regular sequential bond with the hydrogen bond.…”
Section: Chemical and Morphological Characterization Of The Conductiv...mentioning
confidence: 99%